Leading the Future: Exploring Transformational Leadership in the European Animation, Games, and VFX Industries - Hassreiter, Silke; Clavero, Tuki; Bouwels, Lindsey; Perera, A. Treshi-Marie; Haggis-Burridge, Mata (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
This study offers an in-depth analysis of how transformational leadership is currently understood and enacted within the European animation, games, and VFX sectors. Through qualitative insights gathered from 75 professionals across European studios and educational institutions, the research identifies both the promise and the practical limitations of the leadership model that centers on emotional intelligence, mentorship, and shared team ownership. While these principles are widely endorsed in the industries, the study finds that their consistent application is hindered by industry-specific challenges, most notably: the prioritization of technical expertise over leadership capabilities in promotion decisions, a lack of industry-specific leadership training, generational differences, and pressures stemming from intense production demands. Additionally, issues such as blurred boundaries between work and personal life and imbalanced workloads between leaders and teams further complicate leadership in the industries. The findings point to a need for clearer leadership frameworks tailored to the industry’s demands and greater institutional support to equip both current and future leaders with the skills needed to foster sustainable, high-performing teams for the evolving demands of these creative industries.